27.4k views
2 votes
Help Please ASAP!!!!!!!

Help Please ASAP!!!!!!!-example-1

1 Answer

1 vote

Answer:


4x

Explanation:

Step 1: Define

I will substitute delta x with h


\lim_(h \to 0) (2(x+h)^2-2x^2)/(h)

Step 2: Simplify function

  1. Expand:
    \lim_(h \to 0) (2(x^2+2hx+h^2)-2x^2)/(h)
  2. Distribute 2:
    \lim_(h \to 0) (2x^2+4hx+2h^2-2x^2)/(h)
  3. Combine like terms:
    \lim_(h \to 0) (4hx+2h^2)/(h)
  4. Factor:
    \lim_(h \to 0) (h(4x+2h))/(h)
  5. Simplify:
    \lim_(h \to 0) 4x+2h

Step 3: Evaluate limit


\lim_(h \to 0) 4x+2h=\lim_(h \to 0) 4x+2(0)


\lim_(h \to 0) 4x+2(0)=\lim_(h \to 0) 4x+0


\lim_(h \to 0) 4x+0 = 4x

User Methode
by
4.7k points